Investigation of protein secretion and secretion stress in Ashbya gossypii - Aguiar, Tatiana Quinta (2014)
Background: Ashbya gossypii is a filamentous Saccharomycete used for the industrial production of riboflavin that has been recently explored as a host system for recombinant protein production. To gain insight into the protein secretory pathway of this biotechnologically relevant fungus, we undertook genome-wide analyses to explore its secretome and its transcriptional responses to protein secretion stress. Results: A computational pipeline was used to predict the inventory of proteins putatively secreted by A. gossypii via the general secretory pathway. The proteins actually secreted by this fungus into the supernatants of submerged cultures in minimal and rich medium were mapped by two-dimensional gel electrophoresis, revealing that most of the A. gossypii secreted proteins have an isoelectric point between 4 and 6, and a molecular mass above 25 kDa. These analyses together indicated that 1-4% of A. gossypii proteins are likely to be secreted, of which less than 33% are putative hydrolases. Furthermore, transcriptomic analyses carried out in A. gossypii cells under recombinant protein secretion conditions and dithiothreitol-induced secretion stress unexpectedly revealed that a conventional unfolded protein response (UPR) was not activated in any of the conditions, as the expression levels of several well-known UPR target genes (e.g. IRE1, KAR2, HAC1 and PDI1 homologs) remained unaffected. However, several other genes involved in protein unfolding, endoplasmatic reticulum-associated degradation, proteolysis, vesicle trafficking, vacuolar protein sorting, secretion and mRNA degradation were up-regulated by dithiothreitol-induced secretion stress. Conversely, the transcription of several genes encoding secretory proteins, such as components of the glycosylation pathway, was severely repressed by dithiothreitol Conclusions: This study provides the first insights into the secretion stress response of A. gossypii, as well as a basic understanding of its protein secretion potential, which is more similar to that of yeast than to that of other filamentous fungi. Contrary to what has been widely described for yeast and fungi, a conventional UPR was not observed in A. gossypii, but alternative protein quality control mechanisms enabled it to cope with secretion stress. These data will help provide strategies for improving heterologous protein secretion in A. gossypii.